Experimental and modelling study of the torrefaction of empty fruit bunches as a potential fuel for palm oil mill boilers - Sukiran, Mohamad Azri; Abnisa, Faisal; Syafiie, S.; Daud, Wan Mohd Ashri Wan; Nasrin, Abu Bakar; Abdul Aziz, Astimar; Loh, Soh Kheang (Elsevier, 2020)
Empty fruit bunches (EFBs) in the current bulky form are low in energy density and highly moist making them an unattractive option as a solid fuel for producing steam and electricity in palm oil mill biomass boilers. Pre-treatment of EFBs using torrefaction is required in order to improve its energy density via reduction of moisture and oxygen contents, which eventually will lead to an increased high heating value (HHV). In this study, the experiments were conducted in a fixed bed reactor at different feedstock moisture contents (10–67 wt%), residence times (30 and 60 min), and a torrefaction temperature of 270 °C. The distribution of torrefaction products, structural and fuel properties of the torrefied EFBs were investigated with multiple techniques. The results showed that the decrease in the moisture content of feedstock led to a significant increase in the yield of torrefied EFBs. The decrease in moisture content also resulted in increased energy yield and HHV of torrefied EFBs from 52.2% to 99.3% and 18.2–19.2 MJ/kg, respectively. The obtained results were then fitted to a power model to estimate the mass and energy yields of torrefied EFBs at different moisture contents and residence times by using the least squares method. Empirical equations generated by the developed model were accurate and can obtain a satisfactory fit to the experimental data, with the coefficient of determination values higher than 0.96. The calculated energy and carbon stored from the torrefied EFBs offer additional income, clean power, and less pollution in palm oil milling. © 2020 Elsevier Ltd